AKUNTANSI PENJUALAN BERBASIS ONLINE PADA TRAVEL AGENT (Studi Kasus Almadera Hotel Makassar) - Aisyah, Nur; Ramlah, St.; Balfas, Indriani (Patria Artha Journal of Accounting dan Financial Reporting, 2022)
This study aims to determine the accounting for cash sales online travel agents at Almadera Hotel Makassar. The type of data used is descriptive qualitative and quantitative data. Sources of data used are secondary data and primary data. From the results of the study, it can be seen that the description for online cash sales such as traveloka and tiket.com by using an online cash sales accounting system can be seen from the related functions, documents used, accounting records used and procedures used.